Sodium and Potassium Ion Selective Conjugated Polymers for Optical Ion Detection in Solution and Solid State. (16th December 2015) - Giovannitti, Alexander; Nielsen, Christian B.; Rivnay, Jonathan; Kirkus, Mindaugas; Harkin, David J.; White, Andrew J.P.; Sirringhaus, Henning; Malliaras, George G.; McCulloch, Iain
Abstract : This paper presents the development of alkali metal ion selective small molecules and conjugated polymers for optical ion sensing. A crown ether bithiophene unit is chosen as the detecting unit, as both a small molecule and incorporated into a conjugated aromatic structure. The complex formation and the resulting backbone twist of the detector unit is investigated by UV–vis and NMR spectroscopy where a remarkable selectivity toward sodium or potassium ions is found. X‐ray diffraction analysis of single crystals with and without alkali metal ions is carried out and a difference of the dihedral angle of more than 70° is observed. In a conjugated polymer structure, the detector unit has a higher sensitivity for alkali metal ion detection than its small molecule analog. Ion selectivity is retained in polymers with solubility in polar solvents facilitated by the attachment of polar ethylene glycol side chains. This design concept is further evolved to develop a sodium‐salt solid state sensor based on blends of the detecting polymer with a polyvinyl alcohol matrix where the detection of sodium ions is achieved in aqueous salt solutions with concentrations similar to biologically important environments. Abstract : Let's twist: Ion selective small molecules and conjugated polymers undergo a backbone twist in sodium‐ or potassium‐salt solutions. The color change of the polymers is detectable by the human eye and conjugated polymers have a higher sensitivity for ion detection compared to their analogous small molecule. Solid state sensors based on these polymers can detect alkali metal ions in aqueous solutions.